Case of Primary Breast and Ipsilateral Axillary T-Cell Lymphoma: a Rare Occurrence - Faryal Afridi; Garry D. Ruben; Eric Oristian (Case Reports in Surgery)
Background. Malignant lymphomas of the breast are rare and can be primary or secondary. Non-Hodgkin Lymphoma involving the breast is even rarer comprising 0.04-0.5% of all breast malignancies (Takemura). The incidence is even lower for T-cell lymphomas compared with B-cell subtype. We report the rare incidence of primary T-cell lymphoma involving both breast and ipsilateral axilla. Case. This is the case of an 80-year-old female who initially presented with asymmetry of her right breast. Initial mammograms were inconclusive. MRI could not be performed due to the patient’s severe claustrophobia. The patient was then lost to follow-up but re-presented with a new palpable density in the same breast. Subsequent mammogram showed a suspicious lesion with suspicious right axillary lymphadenopathy. Core biopsy was consistent with T-cell lymphoproliferative disorder involving both the breast and the axilla. She was then referred to medical oncology for management. Conclusion. Although rare, lymphoproliferative disorders of the breast can be encountered during workup for suspicious breast lesions. It is imperative that the surgeon is aware of this rare diagnosis to facilitate appropriate therapeutic intervention.